Phytonutritional Content and Aroma Profile Changes During Postharvest Storage of Edible Flowers - Marchioni, Ilaria; Pistelli, Laura; Ferri, Benedetta; Copetta, Andrea; Ruffoni, Barbara; Pistelli, Luisa; Najar, Basma (Frontiers in Plant Science, 2020)
Edible flowers are niche horticultural products, routinely used as cooking ingredients in the food industry. Currently, new species are required with the aim of enlarging the number of species with a long shelf-life, healthy nutraceutical compounds, and new fragrance and tastes. Ageratum houstonianum Mill, Tagetes lemmonii A. Gray, Salvia dorisiana Standl, and Pelargonium odoratissimum (L.) L’Hér “Lemon” were selected for their different morphological characteristics and color. Fresh flowers were analyzed to characterize their phytonutritional content and aroma profile. Postharvest was determined up to 6 days of cold storage at 4°C in transparent polypropylene boxes. Visual quality and cellular membrane damage were observed. The relative content of different antioxidant constituents (e.g., polyphenols, flavonoids, anthocyanins, ascorbic acid), nutritional compounds (soluble sugars, crude proteins), the antioxidant scavenging activity, and the volatile profile were determined and correlated to the quality of shelf-life of the different species. The yellow T. lemmonii freshly picked flowers showed the highest ascorbic acid and flavonoids content, which was maintained during the cold storage, as well as the best visual quality. Limited changes in metabolites were detected in the light blue A. houstonianum during postharvest, although the visual quality is severely compromised. Magenta S. dorisiana and light pink P. odoratissimum showed similar changes in antioxidant constituents during cold storage. For the first time, the volatile compounds have been identified in the four species. Sesquiterpene hydrocarbons are the main class in fresh flowers of A. houstonianum, S. dorisiana, and P. odoratissimum, while monoterpene hydrocarbons are abundant in T. lemmonii. The cold storage influenced mainly P. odoratissimum and S. dorisiana flavor initially dominated by the increase in total monoterpenes at 6 days, reaching a relative content of 90%. Both A. houstonianum and T. lemmonii conserved the prevalence of the same class of constituents in all the analyzed conditions, even though the cold storage influenced the major compound abundance. On the basis of the results, T. lemmonii was the most interesting species with the longest shelf-life due to its phytonutritional and aromatic constituents. Results indicated the peculiar metabolic and physiological attitude of flowers species to cold storage.